Health self-perception and morbidities, and their relation with rural work in southern Brazil - Thais Martins-Silva; Roberta Hirschmann; Caroline Bortolotto; Mayra Fernandes; Ana Carolina Ruivo; Luciana Tovo-Rodrigues (James Cook University, 2020)
Introduction: Self-assessment of health status can be considered a good predictor of population morbidity and mortality. Sociodemographic, environmental and health conditions can influence health self-perception. However, in rural areas, the identification of morbidities that affect workers' health and their general health condition is unknown. This study aims to evaluate the relationship between health self-perception and the occurrence of morbidities according to type of work. Methods: This was a cross-sectional, population-based study of a rural area of Brazil. Health self-perception outcomes were classified as good (very good or good) or not good (fair, poor or very poor). Rural work, classified as yes or no, was considered to be the exposure. Crude and adjusted Poisson regression analyses were performed, obtaining prevalence ratio (PR) estimates and the respective confidence intervals (95%CI). All analyses were stratified by sex and adjusted for confounding factors. Results: The sample comprised 893 individuals. The not good health self-perception prevalence was 27.6%, with a significant difference between the sexes (24.2% of men v 32.5% of women, p=0.014). Although associated with rural work in the crude model, self-perception was not associated with type of work after adjustment (PR: 1.02, 95%CI: 0.83-1.27). The risk of developing obesity (PR: 0.65, 95%CI: 0.47-0.91) and cardiovascular diseases (PR: 0.32, 95%CI: 0.12-0.87) was lower in men who developed rural activities. Also, women who reported doing rural work presented a lower risk for respiratory diseases (PR: 0.47; 95%CI: 0.22-0.97). Conclusion: The association between rural work and not good health self-perception, cardiovascular disease and obesity in women, and respiratory diseases in men seems to be highly dependent on sociodemographic context.